International tax competition: Zero tax rate at the top re-established - Tomer Blumkin; Efraim Sadka; Yotam Shem-Tov (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper we extend the zero tax at the top result obtained in the closed economy case with bounded skill distributions for the case of unbounded skill distributions in the presence of international labor mobility and tax competition. We show that in the equilibrium for the tax competition game the optimal marginal income tax rate converges to zero as the income level tends to infinity. We further show in simulations that the zero marginal tax result is not a local property: over a large range at the higher end of the income distribution, the optimal tax is approximately given by a lump-sum tax set at its Laffer rate. We further show that the range in which the optimal marginal tax is approximately set to zero is widening as migration costs decrease.
Keywords: D60; H20; H50; 330; tax competition; migration; zero marginal tax at the top; Einkommensteuer; Optimale Besteuerung; Steuerwettbewerb; Internationale Arbeitsmobilität; Reichtum; Theorie